High-entropy sodium metal negative electrode and preparation method and application thereof
By using a high-entropy sodium metal negative electrode in sodium metal batteries, the composite structure of a three-dimensional high-entropy conductive framework and a high-entropy sodium-philic alloy phase is used to coordinate the deposition behavior of sodium metal, and the cycle performance and safety problems caused by disordered growth and volume expansion of sodium dendrites are solved, and the high cycle stability and long life of the battery are achieved.
Patent Information
- Application Number
- CN202411937625.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-08
AI Technical Summary
The existing sodium metal batteries have poor circulation performance and safety due to disordered growth of sodium dendrite and volume expansion of sodium metal negative electrode, making it difficult to achieve commercialization.
The high-entropy sodium metal negative electrode is used to recombine the three-dimensional high-entropy conductive framework with the high-entropy sodium-philic alloy to coordinate the deposition behavior of sodium metal. Through the interleaved distribution of the multiphase high-entropy alloy framework and the synergistic effect of the high-entropy alloy phase, the growth and volume expansion of sodium dendrites are inhibited.
It effectively inhibits the generation of sodium dendrites and the volume expansion of the negative electrode, improves the cycle stability and life of the battery, solves the problem of poor circulation performance and safety of sodium metal batteries, and promotes the commercialization process of sodium metal batteries.
Smart Images

Figure CN119786541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-entropy sodium metal negative electrode and a preparation method and application technology, belonging to the field of energy storage technology. Background Art
[0002] Rechargeable lithium-ion batteries have developed rapidly in the past few decades and are widely used in various smart mobile electronic devices and electric vehicles due to their high specific energy and operating voltage, good cycle performance and environmental friendliness. However, the scarcity of lithium resources and unstable cost fluctuations have prompted people to conduct extensive research to seek more cost-effective and reliable energy storage systems.
[0003] Among the many alkaline metal elements, sodium-ion batteries are expected to become a substitute for lithium-ion batteries due to their abundant resources, low cost and similar electrochemical properties to lithium-ion batteries. The optional negative electrodes of sodium-ion batteries are similar to those of lithium-ion batteries, including carbon-based materials, alloy materials, metal oxides and sulfides, among which sodium metal has a higher theoretical specific capacity (about 1166 mAh g -1 ) and low redox potential (about -2.71V, relative to the standard hydrogen electrode potential), it is an ideal negative electrode material for sodium batteries. However, the high reactivity of the sodium metal negative electrode leads to uneven deposition of sodium during the cycle, promoting the disordered growth of sodium dendrites and the formation of inactive sodium. In severe cases, it may pierce the diaphragm and cause a short circuit in the battery, causing the battery to catch fire or even explode. In addition, the sodium deposition without a "host structure" leads to the volume expansion of the sodium metal negative electrode during the cycle, which in turn causes repeated damage / reconstruction of the solid electrolyte interface (SEI) film, continuous consumption of electrolyte and active sodium, and continuous increase in interface impedance, resulting in low coulombic efficiency and poor cycle life of sodium metal batteries, which seriously hinders the commercialization of sodium metal batteries.
[0004] In response to the above challenges, researchers have proposed a number of negative electrode interface engineering strategies as improvement strategies for sodium metal electrodes. For example, by constructing sodium metal electrode interface membranes, such as NaF-polyvinylidene fluoride, tin nanoparticle-polyvinylidene fluoride, Ag-Na3N composite materials, etc., with their high ion diffusion coefficient and high Young's modulus, the controllable and uniform deposition behavior of sodium metal at the interface is achieved to inhibit the growth of sodium dendrites; by preparing organic / inorganic hybrid layers or functional passivation layers, such as using anodized aluminum oxide (AAO) templates to customize one-dimensional array structures with specific spacing and orientation to ensure rapid diffusion channels for sodium ions; by introducing Na 15 Three-dimensional conductive skeletons such as Sn4 act as hosts for sodium deposition, inhibiting volume expansion and dendrite growth. Nevertheless, the stability issues of sodium metal anodes are often interrelated and coupled, and the composite strategy of a single structural component is difficult to provide a comprehensive and systematic solution.
[0005] In recent years, high entropy alloys, as a novel material concept, have attracted attention in many disciplines. Generally speaking, high entropy alloys refer to single-phase crystal structures composed of multiple metal elements, which occupy equal atomic positions in the crystal lattice to maintain a solid solution state. The interface structures of these materials are highly complex and diverse, which not only endows them with rich interfacial chemical properties and reactivity, but also has a profound impact on the comprehensive performance of the materials. Despite this, due to the lack of "host deposition" and instability of the sodium metal anode, it is still a major challenge to achieve precise regulation of its deposition behavior. Summary of the invention
[0006] Technical problem: In order to solve the technical problem of poor cycle performance and safety of sodium metal batteries due to disordered growth of sodium dendrites and volume expansion of sodium metal negative electrodes in the prior art, the present invention proposes a high-entropy sodium metal negative electrode and a preparation method and application. The high-entropy sodium metal negative electrode is composed of a three-dimensional high-entropy conductive skeleton and a high-entropy sodium-philic alloy, which synergistically regulates the deposition behavior of sodium metal. The application of three-dimensional high-entropy skeletons in sodium metal anodes has dual advantages: on the one hand, a variety of sodium alloy skeletons are staggered and distributed as the host structure for sodium deposition. Thanks to their high specific surface area and uniform conductive pathways, they can effectively inhibit the volume fluctuation and dendrite growth of sodium metal during the deposition process, thereby regulating the electric field on the electrode surface and reducing the local current density; on the other hand, the three-dimensional alloy skeleton provides a large number of attachment sites for the sodium-philic alloy phase, which induces sodium metal nucleation and conformal deposition through the synergistic effect of the high-entropy alloy phase, accelerates the decomposition of sodium clusters, greatly reduces the formation of sodium dendrites and "dead sodium", and improves the stability and cycle life of the battery, thereby solving the technical problem of poor cycle performance and safety performance of sodium metal batteries in the prior art due to the disordered growth of sodium dendrites and the volume expansion of the sodium metal anode.
[0007] Technical solution: A high entropy sodium metal negative electrode is prepared by the following method: in the presence of a protective gas, sodium metal and other metals are melted and stirred under a protective atmosphere to obtain a multiphase high entropy sodium composed of a three-dimensional high entropy sodium alloy skeleton and a sodium-philic alloy phase, and after cooling, the high entropy sodium metal negative electrode is obtained by rolling; the required doped metal powder is any three or more of Sb, Bi, Ge, Ag, Sn, Mn, In, Ni, Ca, Au, Zn, K, Mg, Al, and Li powder.
[0008] The method for preparing the high entropy sodium metal negative electrode comprises the following steps:
[0009] (1) polishing a sodium metal block to remove an oxide layer and heating the block to a molten state in the presence of a protective gas;
[0010] (2) adding doped metal powder to high-temperature molten sodium metal, stirring evenly to react fully, and rolling after cooling to obtain a high-entropy sodium metal negative electrode; the doped metal powder is any three or more of Sb, Bi, Ge, Ag, Sn, Mn, In, Ni, Ca, Au, Zn, K, Mg, Al, and Li powder.
[0011] The protective gas is one of argon, nitrogen, helium or neon.
[0012] The heating temperature in step (1) is 280-400°C.
[0013] The amount of each metal element in the doped metal powder is the same.
[0014] The doped metal in the high entropy sodium metal negative electrode accounts for 10-50% of the total mass, and the rest is sodium metal.
[0015] The stirring speed is 600-1500 rpm and the stirring time is 15-60 minutes.
[0016] The thickness of the high entropy sodium metal negative electrode is 10-500 microns.
[0017] The application of the high entropy sodium metal negative electrode in sodium metal batteries.
[0018] The positive electrode is sodium vanadium phosphate or sodium nickel iron manganate, the negative electrode is the high entropy sodium metal negative electrode, and the electrolyte is an ester, ether or sulfone electrolyte using sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, or sodium bis(trifluoromethylsulfonyl)imide.
[0019] Beneficial effects:
[0020] In the present invention, molten sodium metal and other metals are stirred and mixed under a protective atmosphere, and after cooling, a multiphase high entropy sodium metal foil composed of a sodium alloy phase and a non-sodium alloy phase is obtained by mechanical rolling, and the high entropy sodium metal foil is pressed into an electrode sheet to obtain a high entropy sodium metal negative electrode. A multiphase high entropy alloy skeleton is generated in situ during the melting process, and the staggered multiphase skeleton provides a large amount of internal space, which acts as a host to induce the uniform deposition of sodium metal and reduce the volume expansion during the cycle. The high entropy sodium-philic alloy phase loaded on the three-dimensional skeleton improves the sodium affinity of the alloy skeleton, and induces conformal deposition of sodium on the skeleton through its synergistic effect, accelerates the decomposition of sodium clusters, and inhibits the generation of sodium dendrites and inactive sodium, thereby improving the cycle stability and life of the battery; and the preparation process of the high entropy sodium metal negative electrode is simple, and the multiphase structure formed is uniform and stable, which can realize industrial large-scale production, thereby solving the technical problem that the disordered growth of sodium dendrites and the volume expansion of the sodium metal negative electrode in the practical process of the sodium metal battery lead to poor battery cycle performance and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is an X-ray diffraction pattern of the high entropy sodium metal negative electrode of Example 1;
[0022] Figure 2 The scanning electron microscope images of the high entropy sodium metal negative electrode and the sodium metal negative electrode of Example 1;
[0023] Figure 3 Element distribution diagram of the high entropy sodium metal negative electrode of Example 1;
[0024] Figure 4 This is a graph showing the cycling performance test results of a symmetrical battery assembled with a high entropy sodium metal negative electrode according to Example 1;
[0025] Figure 5 This is a graph showing the cycle performance test results of a sodium metal battery assembled with a high entropy sodium metal negative electrode and a sodium vanadium phosphate positive electrode according to Example 1. DETAILED DESCRIPTION
[0026] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the description of these implementations is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various implementations of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0028] In a first aspect, the present application proposes a method for preparing a high entropy sodium metal negative electrode, the method comprising the following steps:
[0029] (1) polishing a sodium metal block in a glove box to remove the oxide layer, and then placing the block in a crucible and heating it to a molten state;
[0030] (2) adding the doped metal powder to the high-temperature molten sodium metal, stirring evenly to fully react, and rolling after cooling to obtain a high-entropy sodium metal negative electrode;
[0031] The doped metal powder is any three or more of Sb, Bi, Ge, Ag, Sn, Mn, In, Ni, Ca, Au, Zn, K, Mg, Al, and Li powder.
[0032] In the present invention, a variety of sodium alloy skeletons with excellent conductivity are generated in situ and staggered inside the negative electrode, reducing the sodium nucleation barrier, acting as a "host structure" to induce uniform deposition of sodium, and effectively inhibiting the volume expansion and dendrite growth of the negative electrode. In addition, the synergistic effect of the high entropy alloy phase can exert the intrinsic properties and complementary advantages of each phase, effectively guide the nucleation and uniform growth of sodium, and promote the uniform deposition of sodium metal on the surface. High entropy alloy is a new concept that has emerged in recent years. The atoms of various elements are randomly and disorderly distributed in the lattice position, thereby affecting the phase stability and microstructure of the material. The lattice distortion produced by the high entropy alloy and the synergistic effect of multiple elements can promote the diffusion of ions in the bulk phase, avoid the volume concentrated burst of a single component, thereby buffering the volume expansion and inhibiting the growth of dendrites. Therefore, introducing a three-dimensional high entropy skeleton loaded with a high entropy sodium-philic alloy phase in the sodium metal negative electrode is an effective way to solve the problem of sodium dendrite growth. At present, high entropy sodium metal has not been used as a negative electrode material for sodium batteries.
[0033] The present invention adopts a melt stirring method to obtain a high entropy alloy material containing pure sodium and a variety of alloy phases, and utilizes the reaction between metal elements and molten sodium to in situ generate a high entropy sodium metal skeleton loaded with a variety of sodium-philic alloy phases. The components of the high entropy sodium metal are closely connected, and the phased, multi-level, and multi-platform sodiumization characteristics are utilized to cooperate and improve the sodium affinity of the skeleton structure and the sodium ion transport performance, effectively inhibit the generation of sodium dendrites and the volume expansion of the negative electrode, and realize the improvement of the cycle performance and stability of the sodium metal negative electrode material.
[0034] The protective gas in the glove box is one of argon, nitrogen, helium or neon, preferably an argon atmosphere.
[0035] The melting temperature of the metallic sodium is 280-400°C, preferably 330°C.
[0036] Preferably, the amount of each metal element in the doped metal powder is the same.
[0037] In the high entropy sodium metal negative electrode, the doped metal accounts for 10-50% of the total mass, and the rest is sodium metal. Preferably, the doped metal accounts for 20% of the total mass, and the rest is sodium metal.
[0038] The stirring speed is 600-1500 rpm, and the stirring time is 15-60 minutes, preferably stirring at 800 rpm for 20 minutes.
[0039] In the preparation process of the high entropy sodium metal negative electrode of the present invention, a multiphase high entropy sodium metal negative electrode consisting of a three-dimensional high entropy sodium alloy skeleton and a high entropy sodium-philic alloy phase is formed during the melting and stirring process, wherein the high entropy sodium alloy skeleton is an alternating structure of any one or more of a sodium alloy skeleton and a non-sodium alloy skeleton, and the high entropy sodium-philic alloy phase is a mixture of any one or more of a sodium alloy phase and a non-sodium alloy phase.
[0040] In a second aspect, the present application proposes a method for preparing a high entropy sodium metal negative electrode, which is prepared by the method for preparing a high entropy sodium metal negative electrode.
[0041] The thickness of the high entropy sodium metal negative electrode is 10-500 microns, preferably 100 microns.
[0042] In a third aspect, the present application proposes an application, which includes a sodium metal battery, wherein the sodium metal battery includes a positive electrode, a negative electrode, a separator and an electrolyte, and the negative electrode is the high-entropy sodium metal negative electrode.
[0043] The electrolyte is an ester, ether or sulfone electrolyte using sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, preferably the solute is sodium hexafluorophosphate, the solvent is diethylene glycol dimethyl ether, and the concentration is 1 mol L -1 .
[0044] The diaphragm is any common diaphragm such as polyethylene diaphragm (PE), polypropylene diaphragm (PP), microporous three-layer membrane (PP / PE / PP), glass fiber diaphragm, etc., preferably Celgard 2325 diaphragm or Whatman glass fiber.
[0045] Example 1
[0046] As for the thickness of the high entropy sodium metal negative electrode, it is preferred that the thickness of the high entropy sodium metal negative electrode is 100 microns, and as for the shape of the high entropy sodium metal negative electrode, it is preferably a disc shape.
[0047] Embodiment 1 provides a method for preparing the high entropy sodium metal negative electrode, comprising the following steps:
[0048] In a glove box, a ceramic blade is used to remove the oxide layer on the surface of the sodium metal block, and the weighed sodium metal block is placed in a nickel crucible. After heating to 330°C, the oxide layer on the surface of the molten sodium is removed, and the weighed mixed alloy powder is added to the nickel crucible. The mixed alloy powder is composed of five single powders of Sb, Sn, Ag, In, and Ge in equal molar ratios, and the mass ratio of the mixed alloy powder to the sodium metal is 1:4. Then, the mixture is stirred and mixed at a speed of 800rpm for 20 minutes. The five metal powders react with the molten sodium to generate high entropy sodium metal, which is rolled after cooling to obtain high entropy sodium metal foil; wherein, the protective gas in the glove box is argon, and the content of water and oxygen is less than 0.01ppm.
[0049] It should be noted that, from the above preparation steps, it can be seen that the preparation method of high entropy sodium metal negative electrode can achieve uniform and sufficient in-situ reaction of five metal powders including sodium metal only through simple melt stirring. The process operation is simple, and the generated negative electrode skeleton is uniform and dense with excellent performance, which is conducive to large-scale production in industrial practice.
[0050] Example 2
[0051] Embodiment 2 provides a method for preparing the high entropy sodium metal negative electrode, comprising the following steps:
[0052] In a glove box, a ceramic blade is used to remove the oxide layer on the surface of the sodium metal block, and the weighed sodium metal block is placed in a nickel crucible. After heating to 400°C, the oxide layer on the surface of the molten sodium is removed, and the weighed mixed alloy powder is added to the nickel crucible. The mixed alloy powder is composed of five single powders of Bi, Mn, Ca, Mg, and Li in equal molar ratios, and the mass ratio of the mixed alloy powder to the sodium metal is 1:3. Then, the mixture is stirred and mixed at a speed of 1500rpm for 45 minutes. The five metal powders react with the molten sodium to generate high entropy sodium metal, which is rolled after cooling to obtain high entropy sodium metal foil; wherein, the protective gas in the glove box is argon, and the content of water and oxygen is less than 0.01ppm.
[0053] Example 3
[0054] Example 3 provides a method for preparing the high entropy sodium metal negative electrode, comprising the following steps:
[0055] In a glove box, a ceramic blade is used to remove the oxide layer on the surface of the sodium metal block, and the weighed sodium metal block is placed in a nickel crucible. After heating to 280°C, the oxide layer on the surface of the molten sodium is removed, and the weighed mixed alloy powder is added to the nickel crucible. The mixed alloy powder is composed of five single powders of Ni, Au, Zn, K, and Sn in equal molar ratios, and the mass ratio of the mixed alloy powder to the sodium metal is 1:6. Then, the mixture is stirred and mixed at a speed of 600rpm for 15 minutes. The five metal powders react with the molten sodium to generate high entropy sodium metal, which is rolled after cooling to obtain high entropy sodium metal foil; wherein, the protective gas in the glove box is argon, and the content of water and oxygen is less than 0.01ppm.
[0056] Example 4
[0057] Example 4 provides a method for preparing the high entropy sodium metal negative electrode, comprising the following steps:
[0058] In a glove box, a ceramic blade is used to remove the oxide layer on the surface of the sodium metal block, and the weighed sodium metal block is placed in a nickel crucible. After heating to 360°C, the oxide layer on the surface of the molten sodium is removed, and the weighed mixed alloy powder is added to the nickel crucible. The mixed alloy powder is composed of five elemental powders of Al, Li, Au, Bi, and Sb in equal molar ratios, and the mass ratio of the mixed alloy powder to the sodium metal is 1:5. Then, the mixture is stirred and mixed at a speed of 1200rpm for 30 minutes. The five metal powders react with the molten sodium to generate high entropy sodium metal, which is rolled after cooling to obtain high entropy sodium metal foil; wherein, the protective gas in the glove box is argon, and the content of water and oxygen is less than 0.01ppm.
[0059] The high entropy sodium metal negative electrode prepared in Example 1 was subjected to structural and performance tests, the structural test including X-ray diffraction test, scanning electron microscopy analysis and elemental analysis, and the performance test including cycle performance test.
[0060] Among them, X-ray diffraction test such as Figure 1 As shown, scanning electron microscopy analysis and elemental analysis are shown Figure 2 , 3 shown; from Figure 1 It can be seen that diffraction peaks of sodium alloy phase and non-sodium alloy phase can be detected on the high entropy sodium metal negative electrode, indicating that sodium and other metals have alloyed, and the added doping elements have also alloyed to form a sodium-philic alloy phase. Further scanning electron microscopy and elemental analysis of the sodium metal negative electrode and the high entropy sodium alloy negative electrode revealed that Figure 2 It can be seen that there are a large number of voids and cracks on the surface of the sodium metal negative electrode, while the surface of the high-entropy sodium metal negative electrode after rolling is relatively flat and has no cracks. The generated various alloy phases are evenly distributed on the surface. These alloy particles act as sodium-philic alloy phases to reduce the nucleation barrier of sodium and reduce the local current density on the electrode surface. The synergistic effect between the various components improves the cycle stability of the sodium metal negative electrode. Figure 3 It can be seen that the sodium alloy skeleton and the sodium-philic alloy phase are evenly distributed in the high-entropy sodium metal anode, and elements such as antimony, tin, silver, indium, and germanium are evenly distributed in the three-dimensional alloy skeleton and the sodium metal surface. On the one hand, the overall stability and sodium affinity of the skeleton are enhanced, inducing the uniform deposition of sodium and alleviating the volume expansion during the sodium deposition process. On the other hand, the electric field distribution on the sodium metal surface is optimized, the decomposition of sodium clusters is promoted, and the two-dimensional deposition mode of sodium metal is realized, thereby improving the electrochemical performance of the high-entropy sodium metal anode.
[0061] The cycle performance of the symmetrical battery assembled with the high entropy sodium metal anode prepared in Example 1 was tested. The high entropy sodium metal anode was assembled into a symmetrical battery in an argon atmosphere glove box, and a constant current charge and discharge test was performed using the Xinwei battery test system. The current density was 2 mA cm -2 , the deposition capacity is 2 mAh cm -2, test its cycle stability during charge and discharge process.
[0062] Performance test results such as Figure 4 As shown. Figure 4 It can be seen that the overpotential of the symmetrical battery assembled with the conventional sodium metal negative electrode is about 50 mV, and the cycle life is about 330 hours. Compared with the symmetrical battery assembled with the conventional sodium metal negative electrode, the high entropy sodium metal negative electrode obtained by the preparation method provided in Example 1 is assembled into a symmetrical battery, and its overpotential is reduced to about 20 mV, and the cycle life is extended to more than 800 hours.
[0063] The cycle performance of the sodium metal battery assembled with the high entropy sodium metal anode prepared in Example 1 was tested. The high entropy sodium metal anode was combined with a sodium vanadium phosphate cathode (10 mg cm -2 ) were assembled into a sodium metal battery in an argon atmosphere glove box, and constant current charge and discharge tests were performed using a Xinwei battery test system with the current set to 1C (1C = 118 mAh g -1 ) to test its cycle stability during charge and discharge.
[0064] Performance test results such as Figure 5 As shown. Figure 5 It can be seen that the capacity of the sodium metal battery assembled with the conventional sodium metal negative electrode decays sharply after about 100 hours of cycling due to factors such as the disordered growth of sodium dendrites and the continuous increase in interface impedance caused by the volume expansion of the negative electrode. Compared with the sodium metal battery assembled with the conventional sodium metal negative electrode, the sodium metal battery assembled with the high entropy sodium metal negative electrode obtained by the preparation method provided in Example 1 still maintains 96 mAh g after 300 cycles. -1 The high discharge specific capacity and capacity retention rate are 92%. This shows that the combination of high entropy sodium alloy skeleton and sodium-philic alloy phase in high entropy sodium metal negative electrode has a significant effect on improving the cycle life of the battery. Compared with the former, the battery based on the use of high entropy sodium metal negative electrode shows the longest cycle life under the test conditions, indicating that the conductive three-dimensional skeleton loaded with high entropy sodium-philic alloy phase can use its synergistic effect to induce the uniform deposition of sodium metal and thus inhibit the growth of sodium dendrites, overcoming the problems of poor cycle performance and short life caused by the disordered growth of sodium dendrites in the actual use of sodium metal batteries, which hinder the industrialization of sodium metal batteries.
[0065] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A high entropy sodium metal negative electrode, characterized in that The method is prepared by the following method: in the presence of a protective gas, sodium metal and other metals are melted and stirred under a protective atmosphere to obtain a multiphase high-entropy sodium composed of a three-dimensional high-entropy sodium alloy skeleton and a sodium-philic alloy phase, and after cooling, the high-entropy sodium metal negative electrode is obtained by rolling; the required doped metal powder is any three or more of Sb, Bi, Ge, Ag, Sn, Mn, In, Ni, Ca, Au, Zn, K, Mg, Al, and Li powder.
2. The method for preparing the high entropy sodium metal negative electrode according to claim 1, characterized in that: The following steps are involved: (1) polishing a sodium metal block to remove an oxide layer and heating the block to a molten state in the presence of a protective gas; (2) adding doped metal powder to high-temperature molten sodium metal, stirring evenly to react fully, and rolling after cooling to obtain a high-entropy sodium metal negative electrode; the doped metal powder is any three or more of Sb, Bi, Ge, Ag, Sn, Mn, In, Ni, Ca, Au, Zn, K, Mg, Al, and Li powder.
3. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The protective gas is one of argon, nitrogen, helium or neon.
4. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The heating temperature in step (1) is 280-400°C.
5. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The amount of each metal element in the doped metal powder is the same.
6. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The doped metal in the high entropy sodium metal negative electrode accounts for 10-50% of the total mass, and the rest is sodium metal.
7. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The stirring speed is 600-1500 rpm and the stirring time is 15-60 minutes.
8. The method for preparing a high entropy sodium metal negative electrode according to claim 2, characterized in that: The thickness of the high entropy sodium metal negative electrode is 10-500 microns.
9. Use of the high entropy sodium metal negative electrode according to claim 1 in a sodium metal battery.
10. The use according to claim 9, wherein the sodium metal battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein: The positive electrode is sodium vanadium phosphate or sodium nickel iron manganate, the negative electrode is the high entropy sodium metal negative electrode, and the electrolyte is an ester, ether or sulfone electrolyte using sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, or sodium bis(trifluoromethylsulfonyl)imide.
Citation Information
Patent Citations
High-entropy lithium alloy negative electrode and preparation method thereof
CN115986064A
Preparation method of multi-component alloy negative electrode for sodium ion battery, battery and application
CN117766691A
Negative-electrode-free modified current collector for sodium battery as well as preparation method and application of negative-electrode-free modified current collector
CN117832512A
High-entropy alloy material used as battery negative electrode and preparation method of high-entropy alloy material
CN118422034A
High-entropy sodium alloy negative electrode, preparation method and sodium battery
CN118448585A
Cited By
High-entropy sodium anode with mixed ion / electron conduction network, preparation method of high-entropy sodium anode and solid-state sodium metal battery
CN120914205A
High-entropy sodium anode with mixed ionic / electronic conducting network and method of making and solid-state sodium metal battery
CN120914205B